The boundary resistance between superfluid 4He near T l and a solid surface - Fu, Haiying; Baddar, Hanan; Kuehn, Kerry; Ahlers, Guenter (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
We report high-resolution measurements of the singular contribution Rb to the thermal boundary resistance between a solid surface and superfluid helium near the superfluid-transition temperature Tl. The results confirm the observation by Murphy and Meyer that a gap between the cell end and the sidewall leads to an apparent finite-current contribution to Rb. In the absence of such a gap, overall agreement of Rb with theoretical predictions is very good. Remaining small differences require further investigations. Without a sidewall gap and within our resolution we found no finite-current effects over the range 3.9╣W / cm 2< Q < 221 ╣uW / cm 2.